Pelatihan Pemberdayaan SDM BUMDes Wisata Salawu - Syamsu Nurkarim; Fatwa Patimah Nursa’adah (Jurnal Ragam Pengabdian, 2025)
The current issues faced by tourist villages are indeed a priority for the Government of the Republic of Indonesia, particularly in relation to tourism-based economic development and community empowerment. In recent years, the development of tourist villages has become a main focus in efforts to improve community welfare, introduce local potential, and support regional development through a sustainable tourism sector.Village-Owned Enterprises (BUMDes) are expected to become an integral part of tourist village communities, providing significant contributions to the development and sustainability of these villages. BUMDes play a crucial role in supporting various economic and social aspects of the village, including resource management, infrastructure development, and community empowerment.However, the challenges currently faced reveal that although BUMDes have great potential to support the development of tourist villages, there are still obstacles that hinder them from providing maximum material support in this context. This has led to the need for independent BUMDes, which not only rely on funding from the government or external parties but also possess the capability to guide and empower the local community directly.One way to achieve this is through training and capacity-building programs focused on improving community skills in managing and developing tourist villages professionally and sustainably. At present, BUMDes Salawu requires competent instructors to gain knowledge from practitioners, which can then be shared widely with the community.